Starch structure and exchangeable protons contribute to reduced aging of high-amylose wheat bread. (15th August 2022) - Li, Caili; Gidley, Michael J.
Highlights: High amylose wheat (HAW) bread has firmer structure than regular wheat bread. HAW bread does not increase in firmness on storage up to 7 days unlike regular bread. HAW bread has more rapid retrogradation due to amylose content and water mobility. Resistant starch levels are much higher for HAW but unchanged on ageing for all breads. Abstract: Breads were prepared from wild-type wheat flour (WTWF) and high-amylose wheat flour (HAWF) with amylose content (AM) 71% and 84%. Melting enthalpy of recrystallized amylopectin (ΔHAP ) increased significantly on storage for wild-type (WT), slightly for 71% AM but not at all for bread with 84% AM. Firmness of bread was positively related to AM content and ΔHAP . Exchangeable proton populations and mobility in high-amylose wheat bread (HAWB) crumb were higher than WT bread measured by 1 H T2 NMR, consistent with the higher water content needed to make doughs from HAWF leading to the crumb network being more plasticized and hindering crumb aging. Although starch recrystallization and bread firming increased, no increase in enzyme-resistant starch (RS) content was observed during bread aging, with RS content only dependent on AM content. Although HAWB has a harder crumb than wild-type, it has greater shelf-life stability and higher nutritional value.